Moyamoya disease with hemorrhagic stroke in a Nepalese woman - Jha, Prabhat; Jha, Binit Kumar; Jha, Rajiv; Bista, Prakash (Nepal Journal of Neuroscience, 2020)
The authors report a case of Moyamoya disease in a middle aged Nepali female. Though the disease is common in other parts of Asia only one case has been reported previously from Nepal. It should be suspected as a rare cause for spontaneous intracerebral hemorrhage in adults.